ANALYSIS OF SHARIA SERVICES AT ZATARANA GUEST HOUSE SYARIAH - Gita Fajar Agustini; Nanda Febriana (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2020)
Indonesia's tourism sector has grown rapidly and significantly. The contribution of high income from the hotel sector shows a significant development, thus affecting the welfare of the community. One of them is the sharia-based tourism sector which is currently developing in various regions, one of which is Bandung. Currently, many people are competing to invest to create Islamic tourism. The tourism industry is of course very closely related to the accommodation business, especially the hotel business. This study aims to examine the Projected Potential of Hospitality Tourism Development with the Concept of Sharia in Indonesia.